Caminhando apesar dos limites : o cuidado parental à criança com retinopatia da prematuridade - Facio, Beatriz Castanheira (Universidade Federal de São Carlos, 2015)
Prematurity has been considered a public health problem. It is a condition, associated with complications, that is among the three leading causes of death in children under age five. It is a risk factor for the development of retinopathy of prematurity (ROP), a vascularization disorder of the immature retina that occurs in eighteen thousand premature infants annually in Brazil, ten percent of which develop visual impairment. Having a premature child with visual impairment due to the retinopathy of prematurity impacts family dynamics. This study aims to analyze the influence of interactions between parents (mother and father) and health professionals in the care of the child with ROP. The theoretical reference is Symbolic Interactionism and the methodological framework is Narrative Research. The data was collected through individual, in depth interviews led by two moments: characterization of the subjects, with elaboration of genogram and eco-map and obtaining the narrative of the phenomenon in focus, through the following proposition: 'I believe that, in function of the prematurity and ROP of your child, you have met with various health professionals. Tell me about your relationship with them and how it interfere in nurturing (child's name). The location of the subjects, parents (father and mother) of children with retinopathy of prematurity, was performed by the snow ball strategy. Questions concerning the characterization of the subjects were an opportunity to create a table with demographic data of both parents and obstetric data from mothers. In addition to a second table concerning children‟s demographics, conditions of birth and received diagnoses during hospitalization in the neonatal intensive care unit. The analysis of parental narratives allowed to list "Walking despite the limits" as the central storyline, supported by the themes "Child‟s Partner" and "(Un)welcoming" (subdivided into Informational and Emotional). These depict the struggle of the parents to nurture the child with ROP before the interactional context with professionals in the studied scenario. We conclude that the interactions with professionals characterized as mostly limited to parental care, especially for the lack of communication and information affecting the creation of bonds, emotional care and the development of parenting skills. On the other hand, interactions with the child and internalized reflections acted as motivating, resulting in partnership actions and stimulating their development. Limitations pointed solely to bringing only parental perspective with almost homogeneous characterization of participants, probably due to the use of snow ball strategy ( probability sampling technique that involves indication of potential subject).The study expands the qualitative evidence in the context of retinopathy of prematurity, with innovative character for lean events inherent to the experience of having / caring for a child with ROP, contemplating the perception of parents (women and men), a fact that breaks the tendency to hear only mothers. The emphasis on interaction has strengthened the value and role of dialogue, of language, of intersubjective interactions as care constituents and thus deserving investment, being still a challenge en route to qualification of Health.
Keywords: Retinopatia da prematuridade; Pais; Pessoal de saúde; Retinopathy of prematurity; Parents; Health Personnel; CIENCIAS DA SAUDE::ENFERMAGEM